Aortic repair following initial decompressive craniectomy for acute type A aortic dissection complicated with extensive hemorrhagic cerebral infarction: a case report - Masaki Kano; Akinari Iwahori; Hitoshi Ogino (Surgical Case Reports)
Abstract A 69-year-old woman presented with acute type A aortic dissection complicated by extensive hemorrhagic cerebral infarction due to brain malperfusion. Emergency decompressive craniectomy was initially performed, with an initial diagnosis of hemorrhagic cerebral infarction. The patient was referred for surgical management following a diagnosis of acute type A aortic dissection. After stabilizing the neurological condition with medical treatment for nine weeks, hemiarch replacement was performed electively. The postoperative course was uneventful, with no new neurological disorders. Subsequently, she recovered sufficiently to have daily conversations and attend hospital appointments using a wheelchair.